Comparative study of induced and spontaneous labour in nulliparous women using modified WHO partograph - Yadav, Kamlesh; Ranga, Monika; Nama, Ankur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induced or spontaneous labour has implication on the eventual mode of delivery and neonatal outcome. The aim of study is to compare mean duration of labour andmaterno-foetal outcome of induced versus spontaneous labour among nulliparous women using modified WHO partograph. Methods: The study was conducted in nulliparous women coming at term in active phase of labour (with cervical dilatation at least 4 cm) either spontaneous or induced, both labouring women were monitored using modified WHO partograph. Outcomes measures include requirement of augmentation of labour with oxytocin, mean duration of labour, eventual mode of delivery and the materno foetal outcome. Results: A total 100 women were compared in each group. There was no difference in mean age group, BMI, gestational age. More women had spontaneous vaginal delivery among those with spontaneous labour (76% versus 58%) (p=0.033). The mean duration of second stage of labour was significantly more in induced labour (16.25 minutes) than in spontaneous labour (14.60 minutes) (p=0.0212). The mean Apgar scores were comparable in two groups. Induced labour is comparable to spontaneous labour regarding fetomaternal outcomes but with increased rate of caesarean deliveries. Conclusions: Study concluded from our study that in spontaneous group mean duration of labour was less than induced group and most of the patient delivered vaginally. In induced group rate of caesarean was higher and requirement of oxytocin for labour augmentation was also more than spontaneous group. Maternal complications were also found more in induced group than spontaneous group whereas neonatal outcome was similar in both the groups. We observed in our study that induced labour can be a safe procedure among nulliparous women if labour is partographically monitored by WHO modified partograph.